2011
DOI: 10.1111/j.1469-8749.2011.04065.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of preterm infant massage on brain electrical activity

Abstract: AIM Early intervention programmes based on the manipulation of the extra-uterine environment have been used in preterm infants with the aim of improving development and functional outcome. Infant massage, among them, has proved effective for weight gain and reduced length of stay in the neonatal intensive care unit. We have recently shown that infant massage accelerates brain maturation of low-risk preterm infants without brain abnormalities as measured by global parameters of electroencephalography (EEG) acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 31 publications
2
74
0
4
Order By: Relevance
“…Evidence of the significant effects of IM on weight gain rate, on stress hormone levels such as cortisol, on growth hormone [7], and on IGF-1 [8] is available in newborns and infants. In preterm infants, it has been shown that body massage influences visual development and affects maturation of cerebral electrical activity [9,10]. In these infants, tactile stimulation probably plays a positive role in neurodevelopment similar to that observed in utero in term infants.…”
Section: Introductionmentioning
confidence: 67%
“…Evidence of the significant effects of IM on weight gain rate, on stress hormone levels such as cortisol, on growth hormone [7], and on IGF-1 [8] is available in newborns and infants. In preterm infants, it has been shown that body massage influences visual development and affects maturation of cerebral electrical activity [9,10]. In these infants, tactile stimulation probably plays a positive role in neurodevelopment similar to that observed in utero in term infants.…”
Section: Introductionmentioning
confidence: 67%
“…45 A range of study methodologies was reviewed, including random ized controlled trials (RCTs), 25,45,[50][51][52][53] follow-up outcomes of these RCTs, 31,52 pretest/ posttest time series interrupted design, 48,54 a quasiexperimental, 46 and an observational, counterbalanced across-session and infants design. 49 Of the and improved neurologic, motor and behavioral development [29][30][31][32] ), many of the existing studies have varying protocols, are limited to healthy or convalescing preterm infants greater than or equal to 32 weeks' postmenstr ual age (PMA), and are seldom contingent on infant cues. In addition, a consensus is lacking on the type of tactile stimulation that is appropriate for high-risk very preterm infants in a level III NICU.…”
Section: Selection Of Eligible Studiesmentioning
confidence: 99%
“…Moreover, a faster EEG maturation was evident in massaged babies, as shown by the more rapid shortening of the interbust intervals, a reliable index of the developmental stage of the brain electrical activity. Interestingly, massaged babies did not exhibit the change in EEG spectral power found in the comparison group [83], confirming that massage intervention affects the maturation of brain electrical activity and suggesting that if may favor a process more similar to that observed in utero in term infants. In good agreement with results obtained in the animal model, massaged infants displayed increased levels of plasma IGF-1 [79].…”
Section: Maternal Enrichment Effectsmentioning
confidence: 62%